Proceedings of SAARC Seminar on Climate Variability in the South Asian Region and its Impacts, Dhaka, Bangladesh, 10-12 December 2002 - Quadir, Dewan Abdul; Prasad, Kanti; Hussain, Md. Amirul (SAARC Meteorological Research Centre, 2003)
Papers presented at the seminar.